2015
DOI: 10.1080/00223891.2015.1077852
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Process of Responding to Circumplex Scales of Interpersonal Values Items: Should Ideal Point Scoring Methods Be Considered?

Abstract: The Circumplex Scales of Interpersonal Values (CSIV) is a 64-item self-report measure of goals from each octant of the interpersonal circumplex. We used item response theory methods to compare whether dominance models or ideal point models best described how people respond to CSIV items. Specifically, we fit a polytomous dominance model called the generalized partial credit model and an ideal point model of similar complexity called the generalized graded unfolding model to the responses of 1,893 college stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…As a result, the criterion validity estimates evidenced by CTT scoring would be expected to be slightly higher in practice, further widening the gap between the two scoring methods. Ultimately, the results presented here are relatively consistent with existing research comparing classical test theory scoring of personality assessments with item response theory counterpart, where IRT-derived scoring does not tend to improve trait estimations (Chernyshenko, Stark, Drasgow, & Roberts, 2007;Ferrando & Chico, 2007;Ling, Zhang, Locke, Li, & Li, 2016;Xu & Stone, 2012), and specifically for selection purposes (Speer, Robie, & Christiansen, 2016). Although TIRT is not without theoretical merits, and assessments constructed with TIRT scoring in mind may be useful for other purposes (e.g., low-stakes, developmental assessments; although more research is certainly required to make that claim), it is clear that applying TIRT scoring to an assessment that was designed to be scored with a CTT methodology may result in inadequate criterion validity.…”
Section: Discussionsupporting
confidence: 86%
“…As a result, the criterion validity estimates evidenced by CTT scoring would be expected to be slightly higher in practice, further widening the gap between the two scoring methods. Ultimately, the results presented here are relatively consistent with existing research comparing classical test theory scoring of personality assessments with item response theory counterpart, where IRT-derived scoring does not tend to improve trait estimations (Chernyshenko, Stark, Drasgow, & Roberts, 2007;Ferrando & Chico, 2007;Ling, Zhang, Locke, Li, & Li, 2016;Xu & Stone, 2012), and specifically for selection purposes (Speer, Robie, & Christiansen, 2016). Although TIRT is not without theoretical merits, and assessments constructed with TIRT scoring in mind may be useful for other purposes (e.g., low-stakes, developmental assessments; although more research is certainly required to make that claim), it is clear that applying TIRT scoring to an assessment that was designed to be scored with a CTT methodology may result in inadequate criterion validity.…”
Section: Discussionsupporting
confidence: 86%
“…The results of this study supported that the AMS items fit to tGGUM that does not assume monotone increasing item characteristics curves. Similar with this result, the studies conducted on instruments measuring various affective skills such as attitude and personality, revealed that the GGUM provided better model data fit than the monotonic models like the GRM (Roberts, Laughling, & Wedell, 1999;Chernyshenko, Stark, Chan, Drasgow, & Williams 2001;Chernyshenko, 2003;Meijer & Baneke, 2004;Chernyshenko, Stark, Drasgow, & Roberts, 2007;Miller, 2007;Cao, Drasgow, & Cho, 2015;Ling, Zhang, Locke, Li, & Li, 2016).…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 67%
“…“speak up” representing an assertive action, “get them to leave me alone” a distancing action, and “tell them when I am annoyed” combining these two actions) [65]. As suggested by previous research, this study will use these dimensional scores instead of the eight octants to predict the outcome [66]. Previous studies in adolescents with ASD have demonstrated acceptable internal consistency of 0.78 for this measure [64].…”
Section: Methodsmentioning
confidence: 99%